TWO TYPES OF ADAKITES IN NORTH XINJIANG, CHINA - Zhao Z.H.; Wang Q.; Xiong X.L.; Zhang H.X.; Niu H.C.; Xu J.F.; Bai Z.H.; Qiao Y.L. (My University, 2006)
Two types of adakites were recognized in northern Xinjiang. The first one is subducted oceanic slab-related adakite and composed of Nb-enriched basalt(NEB) and high-Mg or Mg andesite (HMA or MA). The second one is underplating basalt-related. The first type of adakites were mainly generated during early-middle Devonian-late early Carboniferous (≥320Ma) and distributed in the western Tiansha (Alataw, Boloholo), central Tianshan(Luotuogou), eastern Tianshan(Tuwu-Yandong), south margin of Altay (Fuyun, south Qinghe), central Junggar basin (Luliang) and souther Kalamay (Baogutu). These adakites are characterized by depleted HFSE (Nb, Ta and Ti) and HREE (Yb and Y), enriched in Sr, high positive εNd (t) values, low TDM model ages (<900Ma) and low (87Sr/86Sr)I ratios. The HMA or MA are of high Mg# values, high contents of Cr and Ni and lower positive εNd (t) values. High contents of Nb and relative rich in Yb and Y are the typical features of NEB. These geochemical characteristics for the adakites, HMA and NEB have displayed that the subducted oceanic slab and mantle wedge are the main source materials for these adakite and associated rocks. Particularly, picritic rocks have been found in the south margin of Altay and associated closely spatially and temporally with adakite, HMA and NEB. The second type of adakite was mainly generated in mid-late Permian (≤280Ma) and distributed in Awulale mountain (west Tianshan) and Sanchakou (east Tianshan). No associated NEB and HMA have been found. Based on the distribution of two types of adakites and the close association of the first type of adakites with HMA, NEB and picritic rocks, it can be deduced that the crust accretion in north Xinjiang possesses multi-fashions. For accretion direction, the vertical and horizontal accretion are both exist. For the accretion tectonic process, the oblique subduction of oceanic slab, slab tera, slab window, subduction erosion and the underplating of basaltic materials are all able to generate the adakites, NEB, HMA and picritic rocks. For the accretion materials, there are subducted oceanic slab, mantle wedge, forearc prism, mantle wedge modified by adakitic melt, adakitic melt contaminated by the manle wedge and upwelling asthenospheric thru the slab window. Relatively extensive Cu and Au mineralization associated with adakite, NEB and HMA have been foud in north Xinjiang, particular for the first type of adakites. Some of them can be achive lage-superlarge scale and showing the high potential of adakite, NEB and HMA for the exploration of Cu and Au in north Xinjiang.
Keywords: ADAKITE; CRUST GROWTH; CU AND AU MINERALIZATION; HIGH MAGNESIUM ANDESITE (HMA, MA); NB-ENRICHED BASALT (NEB); NORTH XINJIANG; Палеозой::Пермская; Палеозой::Каменноугольная; Палеозой::Девонская; Paleozoic::Permian; Paleozoic::Carboniferous; Paleozoic::Devonian